Japan : (Distributed in the U.S. by Kodansha America, 1995)
This book shows Information on Japanese culture and history profiles the nation's past, present and future, packing in statistics and facts with a commentary on the nation's growth and development. This isn't a travel guide per say, offering none of the usual itineraries and recommendations for accommodations; but it’s an essential cultural guide reviewed here as a major contribution to understanding the nation as a whole.